Smartphone addiction and loneliness among students - Zahirah Eizzaty Zamr; Junaidah Yusof; Yusma Fariza Yasin; Amalina Ibrahim; Siti Aisyah Panatik; Ang Kean Hua; Norena Abdul Karim Zamri (UTM, 2023)
Smartphones are becoming necessary in an individual’s daily life, especially when everything is within the palm. Smartphone becomes problematic when there is uncontrolled usage, which could harm various aspects. Loneliness can occur when an individual is alone and even surrounded by people. In order to further explore the correlation between smartphone addiction and loneliness, this study is conducted to identify the association between smartphone addiction and loneliness among undergraduate students in Malaysia. A total of 308 undergraduate students were involved in this study. The instruments used were Smartphone Addiction Scale Short Version (SAS-SV) and UCLA Loneliness Scale (Version 3). The results indicate that 60.7% of participants reported having a moderate smartphone addiction, and 42.24% had a moderately high level of loneliness. Pearson’s Correlation results show a significantly weak positive relationship between smartphone addiction and loneliness among undergraduate students. This finding can give insight into smartphone addiction and loneliness, contribute data to future studies, and recommend initiatives to improve undergraduate students’ well-being.